2023
DOI: 10.1186/s13102-023-00678-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiovascular risk factors, disease activity and cardiorespiratory fitness in patients with inflammatory joint disease: a cross-sectional analysis

Abstract: Background Inflammatory joint diseases (IJD) are accompanied by an increased risk of cardiovascular disease (CVD). Cardiorespiratory fitness (CRF) is a modifiable CVD risk factor and low levels of CRF associate with an elevated CVD risk. This study aimed to investigate the associations between CVD risk factors, disease activity and CRF in patients with IJD and to explore differences between patients with normal versus low levels of CRF. Methods CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Although a causal relationship cannot be inferred from these cross-sectional data, a better CRF may result from increased exercise, which also positively affects body composition, blood glucose, and lipid levels. Similar to this study, Nordén et al concluded that patients with in ammatory joint disease and normal CRF had better adipose, HDL-C, and TG levels than those with in ammatory joint disease and low CRF [10]. Moreover, Aspenes et al observed a favorable cardiovascular risk pro le for individuals in the high CRF quartiles, whereas individuals in the low quartiles had increased odds of clustering in CVD risk factors.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although a causal relationship cannot be inferred from these cross-sectional data, a better CRF may result from increased exercise, which also positively affects body composition, blood glucose, and lipid levels. Similar to this study, Nordén et al concluded that patients with in ammatory joint disease and normal CRF had better adipose, HDL-C, and TG levels than those with in ammatory joint disease and low CRF [10]. Moreover, Aspenes et al observed a favorable cardiovascular risk pro le for individuals in the high CRF quartiles, whereas individuals in the low quartiles had increased odds of clustering in CVD risk factors.…”
Section: Discussionsupporting
confidence: 77%
“…Medical background information was collected from the patient's medical records. CRF was assessed by a cardiopulmonary exercise test on a treadmill [10]. A modi ed Balke continuous ramp protocol was applied with the initial speed individualized to the patient's preference.…”
Section: Crfmentioning
confidence: 99%
“…Additionally, IJD associates with an increased risk of CVD, influenced by systemic inflammation and a higher prevalence of classic CVD risk factors [10][11][12]. There are multiple observations of inferior levels of CRF in patients with rheumatoid arthritis [13,14], spondyloarthritis [15,16], and combined diagnoses [17], and low levels of CRF may contribute to the elevated CVD and mortality risk [18,19]. Accurate assessment of CRF is therefore of clinical value in IJD care, as it can shed light on CVD risk and measure the effects of interventions designed to enhance CRF.…”
Section: Introductionmentioning
confidence: 99%